Retrospective Phylogenetic and Molecular Characterization of the S1 Gene of Avian Infectious Bronchitis Virus in Malaysia Highlights Genetic Distinctiveness of Sabah Isolates (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Avian infectious bronchitis (IB) is an economically important poultry disease causing respiratory disease, nephritis, and reduction in egg production in chickens. The aim of this study is to retrospectively study the IB virus (IBV) isolated in Malaysia from the years 2017 to 2018 by characterizing the S1 gene of IBV. Seventeen IBVs were isolated, and the S1 gene was amplified and sequenced. Phylogenetic analysis revealed that three IB lineages, the GI-1, GI-13, and GI-19, were present in the country. Notably, a non-Mass variant that is unique to Malaysia, the MH5365/95 strain, which was once circulated in the country, is not detected in the study. Four S1 protein cleavage recognition motifs, the RRSRR, HRRRR, RRFRR, and RRLDV, were found among the isolates. To the best of current knowledge, this represents the first reported identification of the RRLDV motif in Malaysia. The amino acid variation patterns in the hypervariable regions (HVRs) were found to be distinct among different lineages but similar within the same lineage. Remarkably, IBVs isolated from Sabah exhibit distinct phylogenetic clustering, unique amino acid variation patterns, particularly in GI-1 lineage viruses, and atypical amino acid triplets in the HVRs compared to the Peninsular isolates, indicating regional distinctiveness in IBV evolution within Malaysia, emphasizing the need for more in-depth investigation to determine whether this variation is lineage-specific or influenced by geographic factors. Whole-genome sequencing of the Sabah isolates is crucial for comprehensive characterization of their genetic composition, thereby offering critical insights to inform disease control measures and vaccination strategies. As IBV continues to evolve, further study on its molecular epidemiology, evaluation of existing vaccine efficacy, and cross-disciplinary collaboration are paramount in combating the disease.
Keywords: Avian infectious bronchitis; S1 gene; molecular characterization; Malaysia; Sabah; genetic distinctiveness